Formation nano-sized binary Pt(Pd)-Rh/y- AI2O3+ZrxCe1-xO2 catalysts in high-temperature conversion CO, NOx and carbon hydrоcarbons - A. M. Bolshakov; S. P. Denisov (Тонкие химические технологии)
The article is aimed at solving the problem of directed synthesis of substances with given properties and creation of new functional materials on their base. The concrete fundamental task is chemical design of new multifunctional (TWC) catalysts that ensure simultaneous conversion of carbon monoxide, carbon hydrоcarbons and nitrogen oxides. The main idea of chemical TWC catalyst construction is realization of segregate interaction of NO and CO with the surface substance y-AI2O3+ZrxCe1-xO2